PROTEASE ACTIVITIES OF SEMI-PURIFIED Pseudomonas fluorescens IN PROTEIN DEGRADATION OF PASTEURIZED MILK AT STORAGE - Tatik Khusniati; Irma Normalia (The East Java Biological Society, 2011)
Protein on stored milks spoiled due to protease activities of Pseudomonas fluorescens. To know protease effect on milks, protease activities of semi-purified P. fluorescens on protein degradation in stored pasteurized milks were detected. Protease was semi-purified by ethanol 70%. Protease activities were detected by modified Lowry method, protein degradation by formol titration, and protein content by Kjeldahl method. Milk storage' times were conducted on 0 day (4 days before expired date) up to 12 days (8 days after expired date). The results show that the longer the storage times the higher protease activities and protein degradation of milks. At storage 12 days, protease activities on control were 0.2556 Unit/mL (skim) and 0.2116 Unit/mL (whole), and on inoculated milk (crude) was 2.2044 Unit/mL (skim) and 1.5378 Unit/mL (whole); while on inoculated milk (semi-purified) was 3.5355 Unit/mL (skim) and 1.6778 Unit/mL (whole), respectively. The decrease of inoculated milk' homogeneous were faster than that of control. Protein degradation on control, inoculated skim milks (crude and semi-purified) on 12 days were 4.48%, 7.28% and 7.62%, while that on whole milks were 3.81%, 7.28% and 6.04%, respectively. Based on protease, protein degradation and homogeneous, it can be concluded that skim milk spoiled faster than whole milk.